Differentiate the function f(x) = (x^2 - 1)^3

Using the chain rule: f '(x) = (2x) (3) (x^2 - 1)^2      = 6x(x^2 - 1)^2

Answered by James B. Maths tutor

2738 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Solve x² ≥ | 5x - 6 | (Question from AQA Core 3 June 2016)


find the gradient of the tangent to the curve y=x^2 at the point (4,16)


Why do you get e^x when you differentiate e^x


Find the indefinite integral of 3x - x^(3/2) dx


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences